2024
DOI: 10.1021/jacs.3c12635
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Porous Supramolecular Sorbents for Cobalt Recycling

Keldy S. Mason,
Sheng-Yin Huang,
Samuel K. Emslie
et al.

Abstract: Electronic waste recycling is a recognized global challenge that requires new strategies to bind and release critical materials selectively, such as cobalt present in lithium-ion batteries. To address this challenge, hierarchical 3D-printed porous polymer scaffolds bearing supramolecular receptors were prepared using vat photopolymerization and their cobalt binding profiles were examined as a function of matrix polarity. By combining highresolution digital light processing (DLP) with polymerizationinduced phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Our group previously demonstrated that a glycolamide-based receptor with an all-oxygen tetradentate structure exhibits affinity for lithium and cobalt in anhydrous solvents. Given the limitations associated with anhydrous solvents, we were keen to explore whether cobalt capture and release could be achieved in 95% ethanol.…”
mentioning
confidence: 99%
“…Our group previously demonstrated that a glycolamide-based receptor with an all-oxygen tetradentate structure exhibits affinity for lithium and cobalt in anhydrous solvents. Given the limitations associated with anhydrous solvents, we were keen to explore whether cobalt capture and release could be achieved in 95% ethanol.…”
mentioning
confidence: 99%